1968
DOI: 10.3102/00028312005002203
|View full text |Cite
|
Sign up to set email alerts
|

Time Required to Switch Attention

Abstract: The preferred model of perception presented by writers in the audiovisual field has been one in which information reception can occur simultaneously through different sense modalities. Experimental studies of the last decade, notably those of Broadbent (1958), have cast considerable doubt on the validity of such a model. The data have generally supported a model in which the perceptual system is represented as a single channel, except for the case in which the amount of information arriving is below the inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There has been some debate about the criteria that should be satisfied in order to demonstrate genuinely divided attention (Cave, Bush, & Taylor, 2010; Jans, Peters, & De Weerd, 2010); a consistent concern has been that displays should be designed such that attention cannot be shifted rapidly between elements. Past studies have generally relied on brief presentation times to limit stimulus exposure to durations shorter than the hundreds of milliseconds expected for a spatial shift of attention (Logan, 2005; Reid & Travers, 1968; Remington & Pierce, 1984; Theeuwes, Godijn, & Pratt, 2004). In the present study, we adopted such a strategy by embedding each of two simultaneous targets in an RSVP stream of distracter letters.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some debate about the criteria that should be satisfied in order to demonstrate genuinely divided attention (Cave, Bush, & Taylor, 2010; Jans, Peters, & De Weerd, 2010); a consistent concern has been that displays should be designed such that attention cannot be shifted rapidly between elements. Past studies have generally relied on brief presentation times to limit stimulus exposure to durations shorter than the hundreds of milliseconds expected for a spatial shift of attention (Logan, 2005; Reid & Travers, 1968; Remington & Pierce, 1984; Theeuwes, Godijn, & Pratt, 2004). In the present study, we adopted such a strategy by embedding each of two simultaneous targets in an RSVP stream of distracter letters.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of set and attention that may be found relevant are those by Broadbent (1952aBroadbent ( , 1952bBroadbent ( , 1956Broadbent ( , 1958, Reid a~d Travers (1968), andTalland (1958).…”
Section: Motivation Attitude and Setmentioning
confidence: 99%
“…For example, the work of Travers (1964Travers ( , 1967Travers ( , 1970 and his associates (e.g., Jester &: Travers, 1966;Reid &: Travers, 1968;Van Mondfrans &: Travers, 196^^) extended Broadbent's limited-capacity model to the area of audiovisual communications. These studies generally showed that combined text-audio presentations of redundant information offered no advantage over either of these two channels alone, even when the rate of presenting information was relatively slow (e.g., 200 words per minute or less).…”
Section: Information Processing Theorymentioning
confidence: 99%